Job satisfaction among secondary school teachers - Abdullah, Muhammad Madi; Uli, Jegak; Parasuraman, Balakrishnan (Fakulti Pengurusan, Universiti Teknologi Malaysia, 2009)
This paper provides empirical evidence on the differences in the job satisfaction among secondary school teachers in Sabah with respect to gender, service category, job title, tenure and place of origin. It also attempts to identify the work dimension factors that affect the job satisfaction of the teachers and to ascertain how these factors relate to the aforementioned teachers’ characteristics. A survey was conducted with the participation of 200 teachers. The teachers’ job satisfaction were determined by two separate measures namely overall and facet specific overall job satisfaction. The work dimension factors were clustered into six comprising pay, working conditions, co-workers, promotion, work itself and supervision. This study reveals that secondary school teachers in Tawau, Sabah were generally satisfied with their job; there is a significant relationship between job satisfaction and gender, whereby the male teachers were generally more satisfied than female teachers. The graduate teachers were more satisfied than non-graduate teachers. The higher ranking teachers were more satisfied than the ordinary teachers while the older teachers were more satisfied than their younger counterparts. However, there is no significant relationship between places of origin of teachers with job satisfaction. Based on the bivariate correlation tests, six work dimensions of teaching job are significantly related to teachers’ job satisfaction. In addition, there were significant different between the six dimensions by gender and service category of teachers. Only co-workers dimension is not significantly different among teachers’ career stage and their tenure of service. There was no significant difference between all the work dimensions and teachers’ place of origin. Based on the findings of the study several recommendations are forwarded.